1993
DOI: 10.1364/josaa.10.001841
|View full text |Cite
|
Sign up to set email alerts
|

Binocular enhancement of visual acuity

Abstract: Using a computerized test system, we compared binocular and monocular visual optotype acuity, varying both contrast and contrast disparity between the two eyes. When contrast was the same in the two eyes, binocular acuity was better than best monocular acuity by an average of 0.045 log minimum angle of resolution, or 11%. When contrast differed in the two eyes, binocular acuity in most but not all cases was still better than the monocular acuity of the eye that received the higher contrast. This binocular adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 30 publications
9
55
2
Order By: Relevance
“…Furthermore, the Sensory Station measures of basic visual functions yielded patterns of effects that are in line with previous reports using different measurement methods. Specifically, binocular Static Visual Acuity was better than monocular acuity of either eye (Cagenello, Arditi, & Halpern, 1993); Contrast Sensitivity at 6 cpd was better than 18 cpd, which is consistent with the conical Contrast Sensitivity function showing that medium-level spatial frequencies (~5-7 cpd) are optimally detected compared to low-or high-frequencies (Robson, 1966); Depth Perception thresholds were best in the front facing condition versus looking over the left or right shoulders (Erickson, Yoo, & Reichow, 2010;Yoo, Reichow, & Erickson, 2011); response times for targets on the near screen were significantly faster than on the far screen, supporting previous findings of asymmetries in perceptual processing for near and far targets (Vuilleumier, Valenza, Mayer, Reverdin, & Landis, 1998). These findings provide evidence for the external validity of the Sensory Station as a brief battery of basic visual sensory functions.…”
Section: Perceptual and Visual-motor Abilities As Measured By The Senmentioning
confidence: 88%
“…Furthermore, the Sensory Station measures of basic visual functions yielded patterns of effects that are in line with previous reports using different measurement methods. Specifically, binocular Static Visual Acuity was better than monocular acuity of either eye (Cagenello, Arditi, & Halpern, 1993); Contrast Sensitivity at 6 cpd was better than 18 cpd, which is consistent with the conical Contrast Sensitivity function showing that medium-level spatial frequencies (~5-7 cpd) are optimally detected compared to low-or high-frequencies (Robson, 1966); Depth Perception thresholds were best in the front facing condition versus looking over the left or right shoulders (Erickson, Yoo, & Reichow, 2010;Yoo, Reichow, & Erickson, 2011); response times for targets on the near screen were significantly faster than on the far screen, supporting previous findings of asymmetries in perceptual processing for near and far targets (Vuilleumier, Valenza, Mayer, Reverdin, & Landis, 1998). These findings provide evidence for the external validity of the Sensory Station as a brief battery of basic visual sensory functions.…”
Section: Perceptual and Visual-motor Abilities As Measured By The Senmentioning
confidence: 88%
“…Although computer-based optical simulations with eye models can estimate monocular outcomes [7], it is still unclear how the mechanism of binocular summation behaves in such an unnatural condition of unequal pupils size. Under normal visual conditions, binocular vision is in general superior to monocular vision [8,9]. To quantify the advantage of binocular vision commonly the binocular summation ratio (BSR) is used.…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as the ratio between binocular decimal VA and monocular decimal VA of the better performing eye for according optical conditions. Binocular visual acuity (VA) exceeds monocular VA in the best eye by 11% [8] on average. However, it has also been shown that BSR increases as bilateral contrast decreases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…At the right of the graph, the test is presented to both eyes. Form discrimination sensitivity resulting from binocular presentation is only a little higher than that obtained with monocular viewing (Cagenello, Arditi, & Halpern, 1993), and the binocular advantage is presumably even less when one eye is suppressed. Sensitivity in this case is therefore assumed to be equal to that of the dominant eye and is high regardless of which eye is dominant.…”
Section: Experiments 1 Predictions Of the Hypothesesmentioning
confidence: 70%